The Involvement of Glucose and Lipid Metabolism Alteration in Rheumatoid Arthritis and Its Clinical Implication - Luo TT; Wu YJ; Yin Q; Chen WG; Zuo J (Dove Medical Press, 2023)
Ting-Ting Luo,1,2,* Yi-Jin Wu,1,2,* Qin Yin,1 Wen-Gang Chen,1 Jian Zuo2,3 1Department of Pharmacy, The Second Affiliated Hospital of Wannan Medical College, Wuhu, 241000, People's Republic of China; 2Xin'an Medical Research Center, The First Affiliated Hospital of Wannan Medical College, Wuhu, 241000, People's Republic of China; 3Research Center of Integration of Traditional Chinese and Western Medicine, Wannan Medical College, Wuhu, 241000, People's Republic of China*These authors contributed equally to this workCorrespondence: Jian Zuo, Email zuojian8178@163.comAbstract: Obviously, immune cells like T cells and macrophages play a major role in rheumatoid arthritis (RA). On one hand, the breakdown of immune homeostasis directly induces systemic inflammation; on the other hand, these cells initiate and perpetuate synovitis and tissue damages through the interaction with fibroblast-like synoviocytes (FLS). In recent years, the pathological link between metabolic disorders and immune imbalance has received increasing attention. High energy demand of immune cells leads to the accumulation of metabolic byproducts and inflammatory mediators. They act on various metabolism-sensitive signal pathways as well as relevant transcription factors, such as HIF-1α, and STATs. These molecular events will impact RA-related effectors like circulating immune cells and joint-resident cells in return, allowing the continuous progression of systemic inflammation, arthritic manifestations, and life-threatening complications. In other words, metabolic complications are secondary pathological factors for the progression of RA. Therefore, the status of energy metabolism may be an important indicator to evaluate RA severity, and in-depth explorations of the mechanisms underlying the mystery of how RA-related metabolic disorders develop will provide useful clues to further clarify the etiology of RA, and inspire the discovery of new anti-rheumatic targets. This article reviews the latest research progress on the interactions between immune and metabolism systems in the context of RA. Great importance is attached to the changes in certain pathways controlling both immune and metabolism functions during RA progression.Keywords: rheumatoid arthritis, metabolism, inflammation, immune cells